Empowering Creative Economy MSMEs through Public–Private Partnerships and Digital Transformation - Rizqy Aziz Basuki; Indra Pahala; Puji Yuniarti (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2025)
This study investigates the impact of Public–Private Partnerships (PPPs) and digital transformation on the performance of micro, small, and medium enterprises (MSMEs) in Indonesia’s creative economy sector. Using a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were collected from 120 MSMEs actors participating in collaborative programs between local governments and digital start-ups. The findings reveal that PPPs and digital transformation significantly strengthen the digital capabilities of MSMEs, which subsequently enhance their business performance. Moreover, digital capability functions as a mediating variable that links PPP initiatives and digital transformation efforts to improved MSME outcomes. The results emphasize the importance of multi-stakeholder collaboration among government institutions, private enterprises, and digital innovators in fostering a resilient and competitive creative economy ecosystem. Accordingly, local governments are advised to develop non-infrastructure PPP models that prioritize digital innovation, capacity building, and literacy enhancement for MSME actors.